Impacts of common processes in multistage production system under machine breakdown and quality uncertainties - Wazed, M.A.; Ahmed, Shamsuddin; Yusoff, Nukman (Academic Journals, 2010)
The work desires to determine the optimum level of batch size in bottleneck facility and to analyze the effect of common processes on throughput and cycle time in a production system under uncertain situations created by machine breakdown and quality variation. Few simulation models are developed based on a live case from a company. The models are verified and validated with the historical data from the company and by face validity. Taguchi approach for orthogonal array is used in designing experiments. The experimental settings are executed in WITNESS, a simulation package. It is observed that the variation in level of common process in the system has significant impact on the production quantity and cycle time. The main contribution of this research is determination of the optimal level of batch size in a bottleneck resource under imperfect quality of product and resources breakdown uncertainties. This approach can be generalized to any multistage production system, regardless of the precedence relationships among the various production stages in the system.